Prevalence of Sexual Concerns and Sexual Dysfunction among Sexually Active and Inactive Men and Women with Screen‐Detected Type 2 Diabetes. Issue 4 (1st December 2015) - Bjerggaard, Mette; Charles, Morten; Kristensen, Ellids; Lauritzen, Torsten; Sandbæk, Annelli; Giraldi, Annamaria
Abstract: Introduction: Type 2 diabetes negatively impacts sexual health. Only limited information is available regarding sexual health among sexually inactive patients with type 2 diabetes. Aim: The aim of this study was to examine the prevalence of sexual concerns among sexually active and sexually inactive men and women with type 2 diabetes and of sexual dysfunction (SD) among sexually active. Methods: Data from the Anglo–Danish–Dutch Study of Intensive Treatment in People with Screen‐Detected Diabetes in Primary Care‐Denmark study was used. A total of 1, 170 Danish patients with screen‐detected type 2 diabetes attended a health examination, including assessment of sexual concerns using self‐report questionnaires and of SD using the Female Sexual Function Index (FSFI‐R) and the International Index of Erectile Function (IIEF‐5) instruments. Main Outcome Measures: The main outcome measures used regarding sexual concerns are the following: prevalence of failure to fill sexual needs, of experiencing sexual distress, finding it important to have a good sexual life, and additionally, prevalence of SD. Results: Data regarding sexual activity status during the last 12 months were available among 583 men and 377 women. Seventeen percent of men and 47% of women reported to be sexually inactive, among whom 57% of men and 42% of women reported failure to fill sexual needs; 31% of men and 10% of women that it was important to have a good sexual life, and 32% of men and 11% of women that they were experiencing sexual distress. Around half of men and women were excluded from the SD analysis, mainly because of reporting lack of sexual intercourse during the last 4 weeks. Among those included, 54% of men and 12% of women were found to have SD. Conclusions: Sexual inactivity is highly prevalent among middle‐aged and older men and women with early type 2 diabetes and these patients often have sexual concerns. The high exclusion rates when assessing SD using the FSFI‐R and IIEF‐5 instruments makes it difficult to draw conclusions regarding the prevalence. Sexual health should be broadly assessed in both sexually active and sexually inactive people with type 2 diabetes.